ETHICAL LEADERSHIP: A VERITABLE TOOL FOR NATIONAL TRANSFORMATION, PEACE AND SOCIAL JUSTICE - Gabriel Asuquo; Akerele Peter Adelaja (Universitas Negeri Makassar, 2020)
For sundry reasons, every human community is replete with aberrations of varying magnitude. Some aberrations become so through the criminalisation process by society, some other human acts are considered ontologically uncongenial to human nature. Driving on the left lane of the road in Nigeria, for example, is a traffic offence. It is so because Nigerian road traffic experts consider it convenient to keep right while driving, thereby criminalising driving on the left lane of the road. The aberration of driving on the left lane of the road cannot be said to be adorned with ontological colouration. The phenomenon of rape is considered an ontological aberration in this article and repugnant to human nature. Both the victim and the perpetrator of rape are exposed to social and psychological repercussions. Unfortunately, some of the repercussions on the victim of rape are unnecessary, as they are cosmetically imposed by society, and there is no necessary connection between the aberration and the social consequences. Some of the social and psychological consequences of the phenomenon of rape are considered in this work, and it is argued herein that the social consequences imposed on the victim of rape are unnecessary, and that they unnecessarily compound the traumas that the rape-victim suffers. It is, therefore, suggested herein that some cultural perceptions among most Nigerian tribes should be reviewed to ameliorate the repercussions of rape in the rape-victim.